Influence of steel fibers and microsilica on the mechanical properties of ultra-high-performance geopolymer concrete (UHP-GPC) - Yazan Issa Abu Aisheh; Dawood Sulaiman Atrushi; Mahmoud H. Akeed; Shaker Qaidi; Bassam A. Tayeh (Case Studies in Construction Materials, 2022)
Due to the advantages and challenges specific to geopolymer concrete, especially the ultra-high-performance geopolymer concrete (UHP-GPC) ones, additional studies are warranted. This paper aims to improve the understanding of UHP-GPC by investigating its properties. This research investigates the influence of steel fiber and microsilica (also known as silica fume) on the mechanical characteristics of ultra-high performance geopolymer concrete (UHP-GPC). Three different volume fractions of steel fiber of 0%, 1%, 2%, and 3% and four microsilica volumes by the total mass of the binder of 5%, 10%, 15%, and 25% were utilized. The compressive strength, splitting tensile strength, flexural behavior, and fracture energy are all investigated. Besides, the SEM analyses were performed to understand the mechanism of strength improvement based on the reaction products and micromorphology. The results show that by increasing the amount of microsilica, the amount of steel fiber can be decreased without changing the way UHP-GPC mechanical characteristics.